FEA in Dentistry: A Useful Tool to Investigate the Biomechanical Behavior of Implant Supported Prosthesis - Assunção, Wirley Gonçalves; Barão, Valentim Adelino Ricardo; Gomes, Érica Alves; Delben, Juliana Aparecida; Ribeiro, Ricardo Faria (IntechOpen, 2012)
None